GEOCHEMICAL AND MINERALOGICAL DISTRIBUTION OF GERMANIUM IN THE KHUSIB SPRINGS CU-ZN-PB-AG SULFIDE DEPOSIT, OTAVI MOUNTAIN LAND, NAMIBIA - Melcher F.; Oberthür T.; Rammlmair D. (My University, 2006)
The Khusib Springs deposit in the Otavi Mountain Land, Namibia, is a small though high-grade carbonate-hosted Cu-Zn-Pb-Ag-(As-Sb-Ge) deposit of the "Tsumeb-type" containing approximately 300,000 t of ore grading 10% Cu, 1.8% Pb and 584 ppm Ag. A lens-shaped sulfide orebody, up to 10 m thick and elongated parallel to bedding, replaces limestone, locally brecciated, of the lower Tsumeb Subgroup (Damara Supergroup) in the northern limb of a large NE-trending synclinal structure. A prominent zone of dolomite alteration surrounds the orebody. In a drill core through the orebody, the uppermost 2 m are enriched in Zn (up to 5%) and Ag (up to 3350 ppm), but lower in Ge (<30 ppm) than the central and lower parts of orebody, which are in turn enriched ge (up to 200 pb 7%). massive ore consists a texturally complex mineral assemblage dominated by zn-rich tennantite, enargite, galena pyrite. fe-poor sphalerite is abundant only uppermost part orebody footwall where it forms prominent zone disseminated sphalerite ± chalcopyrite ± galena ± pyrite. The upper zone of the massive ore is further characterized general lack occurrence variety late-stage phases including tetrahedrite, ag-bearing pearceite-polybasite native silver. composed tennantite-enargite-galena with variable proportions pyrite, but lacking sphalerite. most hosted ge-bearing colusite [cu26V2(As,Ge)6 S32] forming small (usually <50 μm in size) grains along the margins of ore layers and veinlets. with notable exception enargite, major sulfides contain only trace amounts ge (<100 ppm). element analyses reveal a wide range concentrations averaging to 500 ppm. frequently, colusite is associated deformed trails phengitic, f-rich muscovite, rutile, apatite, tourmaline, dolomite pyrite. such are interpreted as former stylolites carbonate host rock, which has been replaced by sulfide ore. carries on average 4.0 wt.% ge, up 4.7 w 4.4 sn, occasionally accompanied small mo-w sulfides. additional minerals identified include w-bearing germanite, ge-bearing stannoidite, chalcopyrite, bornite, stromeyerite, chalcocite-group, covellite.
Keywords: COLUSITE; GERMANIUM MINERALIZATION; NAMIBIA; OTAVI MOUNTAINLAND; TENNANTITE; TSUMEB-TYPE DEPOSIT